Diskriminasi Gender terhadap Jurnalis Perempuan di Media - Hafifah Dinda Pratiwi; Sunarto Sunarto; Triyono Lukmantoro (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The background of this research is an organizational structure that is still dominated by men. The aims of this study is describing the essence of the experience of gender discrimination that afflicts female journalists in the media also the efforts made by female journalists in order to fight for her rights in the media. This type of research is descriptive using a critical paradigm. The subjects of this study consisted of three female journalists from different types of media such as print media, television, and online media. The study's findings reveal that there is gender discrimination in the media include sexual harassment, coverage burden, menstrual leave, availability of lactation room, career level, and availability of childcare space. There are also efforts made by female journalists to fight such as joining journalist organizations and unions outside the company, doing deals, talking to superiors, and exploring studies on gender. Gender discrimination occurs due to a culture of patriarchy that is entrenched in the media such as a smaller number of female journalist, dominant male mindset, lack of understanding gender affirmation, placement of journalist coverage, lack of women in the position of media editor, and the double burden that befalls female journalists.